A new modeling of planetary gear set to predict modulation phenomenon. (15th July 2019) - Zghal, Bacem; Graja, Oussama; Dziedziech, Kajetan; Chaari, Fakher; Jablonski, Adam; Barszcz, Tomasz; Haddar, Mohamed
Highlights: A lumped parameters model of a planetary gearbox is developed in order to simulate all vibration sources. The time varying transmission path is modeled implicitly in the dynamic model to simulate the amplitude modulation phenomenon. An analysis of vibration characteristics is done and compared with experimental laboratory data in frequency domain. Abstract: Modeling planetary gearbox helps people understanding its dynamic behavior. In addition, it can be a useful tool to simulate faults either simple or combined to know what is the signature of a such fault in the dynamic behavior. Hence, the cost can be reduced comparing with experiments. In addition, it can help designers who developed new planetary gearbox in order to create a gearbox with minimum level of vibration energy by playing on geometric and physical parameters. As known, a sensor mounted on a planetary gearbox is subject to vibration signal generated primary by the meshing of gears and influenced by the position of planets. Therefore, a lumped parameter model is proposed to simulate vibration sources. The novelty of this work is centered around modeling the time varying transmission path. This latter is implicitly done by expressing all displacements at the sensor location before the resolution of the equation of motion. Vibration characteristics are analysed and validated by experimental laboratory data in frequency domain.